Binary Logistic Regression Analysis of the Relationship Between Lunar Month of Diagnosis of Autoimmune Hepatitis and Treatment Options - Gadour, Eyad; Phyu, N; Ahmed, Omar; Elamin, Hiba (International Journal of Innovative Research in Medical Science, 2023)
Immunosuppressive has been the main treatment for patients with moderate or severe autoimmune hepatitis (AIH) as the survival benefits have clearly been demonstrated in clinical trials. Seasonal variations in treatment have not been studied yet, hence, we aim to study the potential relationship between the Lunar month of diagnosis and treatment options in AIH. All cases of AIH who presented to our hospitals between Jan 2016 and Jan 2021 were reviewed. Data was analyzed using the binary logistic regression model and Chi-square test of association to establish any potential relationship between the Lunar month of diagnosis and treatment response in AIH. Total number of patients with clinically and histologically proven AIH was sixty. Forty-seven were females (78.33%) and 28.33% were males (n=17). Liver biopsies were recorded in twenty-six cases (43.3%) among whom, interface hepatitis was found in ten patients (16.7%). Total of twelve patients were not on any treatment and five of them (41.6%) had been diagnosed during the Full Moon (FM) phase. Patients who have been diagnosed with AIH during the Third Quarter (TQ) Phase were only three (5.0%), however 66.6% of them were on combination therapy of Steroids and Azathioprine (AZA). Interestingly, fifth of the patients were diagnosed during the First Quarter phase and only one of them were on combined therapy. Ten patients in total were on steroids only among whom 40% were diagnosed during the FM phase. The Chi-square test of association showed a non-significant association of the lunar month of diagnosis with the treatment they receive, X2 (9, N= 31) = 7.99, p = .535. Steroids and AZA treatment exhibited lower frequency on full moon and third quarter moon than new and first quarter moon. Our data show that patients diagnosed with AIH during the FM phase of the lunar cycle are less likely to require combination therapy of steroids and AZA. We could not establish any significant relation between the lunar month of diagnosis and treatment response in AIH.